The impact of diagnosis-related group payment on the hospitalization expenditure and medical quality of public hospitals in China - Mei Zhou; Yufan Mao; Zizhuo Jiao; Liangrong Zhou (PLoS ONE, 2025)
Background Healthcare expenditures in China have been rising rapidly in recent years. To reform the medical insurance payment system, China has introduced Diagnosis-Related Groups (DRG) to maintain quality. But does excessive control of hospitalization expenditures affect the quality of care? This study analyzes the implementation of DRG in Chinese public hospitals to examine its impact on both hospitalization expenditures and quality of care. Methods Based on data from the Hospital Information Systems (HIS), Electronic Medical Records (EMR), and the DRG management platform in Hunan Province, this study utilized a random sampling method to select hospitalization data. The analysis included 49,192 cases from four public hospitals, encompassing periods before(n = 23,494) and after(n = 25,698) DRG implementation. Additionally, data from two other public hospitals were randomly selected, comprising 7,969 cases before and after the introduction of hospital administrative interventions following DRG implementation (3,862 pre-intervention and 4,107 post-intervention). Statistical analyses comprised descriptive statistics, t-tests, chi-square tests, multiple linear regression, and multivariate logistic regression. Results After DRG implementation, the logarithmic mean of total hospitalization expenditures decreased significantly (3.914 ± 0.837 vs. 3.872 ± 1.004), while rates of unplanned readmissions, unplanned reoperations, postoperative complications, and patient complaints within 30 days increased significantly (3.784% vs 4.214%, 0.083% vs 0.166%, 0.207% vs 0.258%, 3.741% vs 5.133%). The proportions of grade IV surgeries and critical patients also decreased (42.602% vs 46.174%, 16.943% vs 18.001%). Adjusted linear regression indicated DRG implementation was negatively associated with the log mean of costs (β = –0.002, 95% CI: – 0.003, – 0.001), a 0.2% reduction. In logistic regression, DRG was not significantly associated with mortality or nosocomial infection, but was positively associated with postoperative complications (OR = 1.16, 95% CI: 1.12, 1.20) and patient complaints (OR = 1.32, 95% CI: 1.01, 1.75).Post-DRG, provincial hospitals had higher values than municipal hospitals in log mean costs, proportion of critical patients, and Grade IV surgeries (3.897 ± 1.024 vs. 3.857 ± 1.012; 19.568% vs. 16.463%; 47.252% vs. 39.371%). Before DRG, provincial (vs. municipal) hospitals showed no association with hospitalization expenditures, critical illness proportion, or mortality, but had 1.19 times the Grade IV surgery proportion (OR = 1.19, 95% CI: 1.08, 2.32). After DRG, these became 1.004, 1.34, and 1.44 times higher, respectively, with no mortality association. After administrative intervention, increases occurred in nosocomial infection, unplanned reoperation, 30-day readmission, patient complaints (5.955% vs. 5.040%; 0.186% vs. 0.000%; 4.065% vs. 3.324%; 4.868% vs. 3.360%), and log mean costs (3.898 ± 1.253 vs. 3.963 ± 0.884). Mortality and postoperative complications did not change significantly (0.40% vs. 0.463%; 0.279% vs. 0.189%). Linear regression indicated a positive association between intervention and expenditures (0.5%increase). Logistic regression showed negative associate with mortality, infection, complications and patient complaints corresponding to risk reductions of 2%, 7%, 4% and 3% respectively. Conclusions The DRG payment system effectively controlled the growth of hospitalization expenditures in Chinese public hospitals. However, an exclusive focus on expenditure containment may adversely affect medical quality. Appropriate administrative interventions can help improve medical quality while managing expenditures.